2015
DOI: 10.1039/c5dt02908b
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Zr-based MOFs with alkyl and perfluoroalkyl groups: the effect on the water sorption behavior

Abstract: Stability and sorption of Metal-Organic Frameworks (MOFs) towards water are critical in many applications, and can a priori be modulated through the introduction of suitable organic functional groups on their backbone. We report here the preparation of a series of Zr(iv)-based MOFs functionalized with alkyl and perfluoroalkyl groups and their characterization by X-ray powder diffraction, multi-nuclei ((1)H, (13)C, (19)F) solid state nuclear magnetic resonance analyses, and nitrogen sorption measurements at 77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…In the targeted applications where adsorption is the main process, the surface chemistry of materials is indeed of prime importance . In the case of MOFs, several strategies have been undertaken in order to adapt the affinity of the host network either for favoring or disfavoring interactions with sorbates: (i) the post‐synthetic or in situ functionalization of the framework; (ii) the modification of the CUS nature or their saturation to prevent strong interactions between the metal center and sorbate molecules; or (iii) the introduction of extra‐framework charges by using for instance hydrophilic alkali or hydrophobic organic cations . In all these cases, the hydrophobic/hydrophilic character of the network is governed by the nature of the organic functionalities, metal ions, CUS, which modify the hydrophilic/hydrophobic balance by varying the nature of the interactions (strong covalent interactions, electrostatic or van der Waals interactions, H‐bond interactions and hydrophobic interactions) of the solid network with guest species.…”
Section: Figurementioning
confidence: 99%
“…In the targeted applications where adsorption is the main process, the surface chemistry of materials is indeed of prime importance . In the case of MOFs, several strategies have been undertaken in order to adapt the affinity of the host network either for favoring or disfavoring interactions with sorbates: (i) the post‐synthetic or in situ functionalization of the framework; (ii) the modification of the CUS nature or their saturation to prevent strong interactions between the metal center and sorbate molecules; or (iii) the introduction of extra‐framework charges by using for instance hydrophilic alkali or hydrophobic organic cations . In all these cases, the hydrophobic/hydrophilic character of the network is governed by the nature of the organic functionalities, metal ions, CUS, which modify the hydrophilic/hydrophobic balance by varying the nature of the interactions (strong covalent interactions, electrostatic or van der Waals interactions, H‐bond interactions and hydrophobic interactions) of the solid network with guest species.…”
Section: Figurementioning
confidence: 99%
“…21 Functionalizing the organic ligands of MOFs is an effective method to adjust the performance of MOFs. There have been systematic studies on the functionalization of organic ligands in many elds, such as gas storage, 22 catalysis 23 and adsorption. 24 In addition, researchers have used functionalized MOFs to improve the performance of drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…By assuming that the pores are occupied by water in a liquid or quasi‐liquid status at a pressure near P 0 , a theoretical water adsorption capacity (CH2OT) can be calculated by Equation , where ρ stands for the density of water confined in a pore and V is the pore volume determined experimentally. In the literature, either the density of liquid water (1 g cm −3 ) or the density of crystallized water (ice) (0.9168 g cm −3 ) was adapted as ρ in the calculation. A comparison of the calculated CH2OT and CH2O determined from water adsorption experiments offers information about how hydrophobic the adsorbent is.…”
Section: Assessment Of Hydrophobicity In Mofsmentioning
confidence: 99%
“…UiO‐66−1,4‐Naphyl was thus regarded as a promising adsorbent for gas separations under humid conditions. Yu et al studied the water adsorption properties of 6 UiO‐66 analogues, UiO‐66D‐(CF 3 ) 2 , UiO‐66‐(C 2 H 5 ) 2 , UiO‐66‐C 2 F 5 , UiO‐66‐(CF 3 ) 2 , UiO‐66‐CH 3 , UiO‐66‐(CH 3 ) 2 , and UiO‐66‐CF 3 , obtained by alkyl‐ and perfluoroalkyl‐functionalized 1,4‐H 2 bdc ligands . The authors also showed that the water adsorption behaviors were affected by both the hydrophobicity of the functional group and the effect of pore reduction.…”
Section: Preparation Of Hydrophobic Mofsmentioning
confidence: 99%
See 1 more Smart Citation